Visualization of HSP70-regulated mild-photothermal therapy for synergistic tumor treatment: a precise space-time mild-temperature photothermal ablation strategy - Binyue Zhang; Yanchun Ma; Qi Liu; Shutong Wu; Lin Chen; Chunmei Jiang; Haonan Chen; Hongyan Jia; Ziliang Zheng; Ruiping Zhang (Journal of Nanobiotechnology)
Abstract Mild-temperature photothermal therapy (MPTT) advances anticancer management by regulating reactive oxygen species (ROS) and lipid peroxides (LPO) to inhibit the overexpression of heat shock protein 70 (HSP70), thus decreasing the cellular heat resistance and increasing the efficacy of tumor ablation. However, formidable challenge remains on the traditional MPTT without imaging-guided optimal treatment time point, thus inadequate HSP70 blockage would potentially further diminish the effectiveness of MPTT. Herein, a novel biomimetic nanoprobe (Cu-ABTS@CCMs) is developed, based on encapsulating the multifunctional Cu nanoparticles and ROS-responsive 2,2′-azino-bis (3-ethylbenzothiazole-6- sulphonic acid) (ABTS) within cancer cell membranes (CCMs) to ensure second near-infrared photoacoustic (NIR-II PA) imaging-guided precise MPTT time point. The core Cu nanoparticles achieve highly effective HSP70 blockage via a nearly simultaneous cascade of photocatalytic O2-generation and dual ROS/LPO accumulation. Triggered by self-enhanced ROS/LPO up-regulation, the ABTS can correspondingly oxidize to ABTS•+, which further leads the real-time ratiometric PA signals (ABTS•+-PA730/Cu-PA960) that show highly accurate visualization of ROS and quantitatively convert into dynamic tracking of the changes in HSP70 blockage. The intelligent dual-modality imaging information will provide more possibilities for the optimal time-point and site-specificity of MPTT and potential avenues for the development of clinical breast cancer treatments.